Enhancement production biogas from palm oil mill effluent (POME) - Nuruliana, Ismail (2012)
Energy demand is increasing continuously due to rapid growth in population and industrialization development. The major energy demand is provided from the conventional energy sources such as coal,oil,natural gas,etc.In every country is facing with these conventional fuels, are depletion of fossil fuels and deterioration of environment. Meanwhile,the Malaysian oil palm industry is an important industry but the waste organic from palm oil mill effluent (POME) is a contributed to global warming phenomena.The experiment for capture gas methane will be one of the alternative ways to encounter this problem.It investigated to increase the gas CH4 and decrease the gas CO2 to a biogas production.The parameters that have been focused throughout identified condition temperature and monitoring optimum day in bioreactor.Gas Chromatography is used to detect the concentration time in weekly for one month.Temperature in the pilot plant is not to control but the result is take for analysis.Meanwhile the pattern of the concentration CH4 by a weekly was taken. The study shows,the mesophilic condition is highest concentration methane than thermophilic condition. POME in the bioreactor 500m3 after a fortnight needed to discharge and uploads a quarter of volume in bioreactor to get optimum condition. As a conclusion, the applicability of temperature and time in bioreactor was enhancement the biogas production and can be used to generate electricity. Biogas capture also has resulted in substantial greenhouse gasses (GHG) reduction.